Dysnumeria in Sign Language: Impaired Construction of the Decimal Structure in Reading Multidigit Numbers in a Deaf ISL Signer - Friedmann, Naama; Haluts, Neta; Levy, Doron (Frontiers in Psychology, 2021)
We report on the first in-depth analysis of a specific type of dysnumeria, number-reading deficit, in sign language. The participant, Nomi, is a 45-year-old signer of Israeli Sign Language (ISL). In reading multidigit-numbers (reading-then-signing written numbers, the counterpart of reading aloud in spoken language), Nomi made mainly decimal, number-structure errors– reading the correct digits in an incorrect (smaller) decimal class, mainly in longer numbers of 5-6-digits. A unique property of ISL allowed us to rule out the numeric-visual analysis as the source of Nomi's dysnumeria: In ISL, when the multidigit-number signifies the number of objects, it is signed with a decimal structure, marked morphologically (e.g., 84 Eight-Tens Four); but a parallel system exists (e.g., for height, age, bus numbers), in which multidigit-numbers are signed non-decimally, as a sequence of number-signs (e.g., 84 Eight, Four). When Nomi read and signed the exact same numbers, but this time non-decimally, she performed significantly better. Additional tests supported the conclusion that her early numeric-visual abilities are intact: she showed flawless detection of differences in length, digit-order, or identity in same-different tasks). Her decimal errors did not result from a number-structure deficit in the phonological-sign output either (no decimal errors in repeating the same numbers, and in signing multidigit-numbers written as Hebrew words). Nomi had similar errors of conversion to the decimal structure in comprehension of numbers (number-size comparison tasks), suggesting that her deficit is in a component shared by reading and comprehension. We also compared Nomi's number-reading to her reading and signing of 406 Hebrew words. Nomi's word-reading was in the high range of the normal performance of hearing controls and of deaf signers and significantly better than her multidigit-number reading, demonstrating a dissociation between number-reading, which was impaired, and word-reading, which was spared. These results point to a specific type of dysnumeria in the number-frame generation for written multidigit-numbers, whereby the conversion from written multidigit-numbers to the abstract decimal structure is impaired, affecting both reading and comprehension. The results support abstract, non-verbal decimal structure generation that is shared by reading and comprehension, and suggest the existence of a non-decimal number-reading route.